Transforming human trafficking rescue services in Nigeria: towards context-specific intersectionality and trauma-informed perspectives. Issue 7 (29th September 2021) - Badejo, Foluké Abigail; Gordon, Ross; Mayes, Robyn
Abstract : Purpose: This study aims to introduce context-specific intersectionality and trauma-informed perspectives for transformative services theory and practice. While transformative service research concerning vulnerable people has focused on well-being and alleviating suffering, there has been less attention paid to how the intersection of scales of social categorisation such as class, gender and cultural norms shapes experiences and outcomes. Likewise, there is a paucity of attention to how lived experiences of trauma among people, such as human trafficking survivors, can and should influence service interactions, delivery and outcomes. Design/methodology/approach: The authors draw upon insights from a focused ethnographic study featuring narrative interviews with ten human trafficking survivors and seven rescue service industry stakeholders, as well as field observations, in Nigeria. Thus, this work enriches the limited scholarship on transformative services across Africa, where local cultural contexts have a significant influence on shaping service environments. Findings: The authors identify how the intersections of socio-economic class, gender dynamics, cultural norms and trauma shape the service experience for survivors. Originality/value: The authors argue for the criticality of intersectionality and trauma-informed perspectives to transformative services to improve the mental and economic well-being of survivors of human trafficking in the long term.